Facies and sequence stratigraphy of a mixed carbonate-volcaniclastic ramp in intra-arc settings: an example from the Toqui Formation (Lower Cretaceous), southern Chile (45°S) - Rivas, Hermann; Salazar Soto, Christian; Stinnesbeck, Wolfgang (Journal of South American earth sciences, 2021)
The Toqui Formation in the Northern Austral Basin, or Aysén - Río Mayo Basin in Central Patagonia (43°-49°S), is the basal member of the transgressive-regressive Coyhaique Group of Tithonian-Aptian age. A revision of the basin fill, focusing on the early transgressive units exposed in Chile and Argentina at 45°-46°S, is presented. In order to explain the lithological variability of the mixed calcareous-volcaniclastic Toqui Formation and the evolution of its depositional environments, a detailed sedimentological-petrographic analysis of two outcrops and four drill cores was executed at the type locality, El Toqui Mine (45°S). Twenty-three lithofacies were recognized, arranged in five facies associations. The Toqui Formation comprises three facies associations (Calcareous-; Muddy-, and Sandy Volcaniclastic), and is here redefined as conformed by two members: Manto- and Mina San Antonio Members. Its Manto Member conformably overlies volcanic rocks of the Ibáñez Fm., settled as subtidal Gilbert-type delta foresets, conforming a proximal-medial volcanic apron (Kimmeridgian-Valanginian). The Manto Member includes mixed calcareous-volcaniclastic sandstone, bioclastic wacke-floatstone, and oyster boundstone, depicted as patch-reefs developed in a carbonate mid- and outer-ramp. The Manto Member is covered by tuffaceous mudstone and volcanic sandstone of the Mina San Antonio Member, representing a prograding, eruption-fed shelf delta, conforming a medial-distal volcanic apron. Upsection, the volcaniclastic succession retrogrades into outer-shelf hemipelagic mudstone of the Katterfeld Formation. Overall, the Aysén Basin depicts a not fully developed marginal basin, i.e. formed by extension but without onset of seafloor spreading. The early marine transgression is linked to a relative sea-level rise caused by tectonic subsidence (back-arc extension), and the subsequent flooding of continental, intra-arc volcanic terrains comprising a transgressive system tract. Carbonate platforms aggraded as highstand system tracts over the subtidal volcanic topography, suggesting periods of tectono-volcanic quiescence. Ramps were covered by prograding deltaic deposits, reflecting a normal regression caused by high volcaniclastic input and local, shallow intrusion-related volcanic uplift (inflation). Upwards, the volcaniclastic succession grades to prodelta and hemipelagic deposits of a major transgressive system tract. The onset of pelagic conditions depicts an important relative sea-level rise, regarded as caused by “post-rift” thermal subsidence, possibly enhanced by the Valanginian high global eustasy. Lithological differences between the Toqui Formation in Chile and the partly coeval transgressive units exposed in Argentina (44°50′-47°S), i.e. Cotidiano, Tres Lagunas, and Springhill Formations, is considered as caused by diachronic development of ramps, lateral facies changes, and differential volcaniclastic input. Deposition of the Toqui Formation thus reflects a complex interaction between tectonic subsidence, coastal volcanism, and patch-reef growth.
Gesehen am 15.07.2021